2011
DOI: 10.1111/j.1466-7657.2010.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Work/life balance and health: the Nurses and Midwives e‐cohort study

Abstract: Using an internationally novel web-based approach, a large cohort, which appears generally similar to population norms, has been established. Provided participant retention is adequate, the NMeS will provide insight into understanding the drivers of nurses' and midwives' workforce retention and work-related factors associated with their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 31 publications
(37 reference statements)
6
81
0
1
Order By: Relevance
“…Most nurses are also dissatisfied with inflexible work schedule, shift work and low salary [17,18]. Nursing is a female-dominated job and women are usually the primary caregivers of family members [19]. However, female workers in traditional societies such as Iran might face more demanding family roles because family means not only parents and children but also the extended family, and even neighbours and friends [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most nurses are also dissatisfied with inflexible work schedule, shift work and low salary [17,18]. Nursing is a female-dominated job and women are usually the primary caregivers of family members [19]. However, female workers in traditional societies such as Iran might face more demanding family roles because family means not only parents and children but also the extended family, and even neighbours and friends [6].…”
Section: Introductionmentioning
confidence: 99%
“…Details of the NMeS have been reported elsewhere. [18][19][20] Briefly, the DeC Study aimed to be a 5-year cohort study using a purpose-built internet-based survey (see http://doctors.e-cohort. net).…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…All participants had a unique ID generated automatically at registration. [18][19][20] Data processing and statistical analysis Data were copied from the SQL database into SAS ® software, Version 9.2 (SAS Institute Inc., Cary, NC, USA) where data cleaning was undertaken. Participants were not personally identified in analysis datasets; all datasets included the participant ID only.…”
Section: Data Storage and Securitymentioning
confidence: 99%
“…Several authors have investigated and reported that stressor is any relationship between the person and the environment that is perceived by the person as taxing. The relationship can result in either a beneficial or a harmful outcome (Sonnentag et al, 2010;Schluter et al, 2011;Bakibinga et al, 2012). And have found that different types of stress produce anxiety in individuals, which results in feelings of apprehension that can ultimately lead to negative physical, emotional, cognitive and behavioral symptoms (Boyd & Nihart, 1998).…”
Section: Introductionmentioning
confidence: 99%